PHYSICOCHEMICAL AND MICROBIOLOGICAL CHARACTERIZATION OF NAUCLEA LATIFOLIA AND PILIOSTIGMA THONNINGII MACERATES USED IN TRADITIONAL MEDICINE FOR THE TREATMENT OF MALARIA - TRAORE Moumouny; KOUAME N´zebo Desire; YORO Thierry Dezay; SANOGO Seydou; TOURE Abdooulaye (GSC Biological and Pharmaceutical Sciences, 2026)
Macerates of Nauclea latifolia and Piliostigma thonningii are used by the population of Korhogo for their antimalarial properties. However, the risk of microbial proliferation in the macerate is significant. The overall objective was to determine the physicochemical and microbiological parameters of Nauclea latifolia and Piliostigma thonningii macerates. For the preparation of the macerates, tap water was added to the roots of Nauclea latifolia and the bark of Piliostigma thonningii on day D0. The evolution of the microbial flora and physicochemical parameters were monitored from D0 to D12. All analyses were carried out according to international standards. The loads of Aerobic Focal Mesophilic Microorganisms, total and thermotolerant coliforms, Escherichia coli, S. aureus, and molds increased from 3.15 to 8.89 log10 CFU/mL and 3.34 to 8.51 log10 CFU/mL; 2.31 to 7.87 log10 CFU/mL and 2.39 to 7.8 log10 CFU/mL; 2.0 to 7.94 log10 CFU/mL and 2.18 to 7.63 log10 CFU/mL; 1.74 to 6.6 log10 CFU/mL and 1.96 to 6.71 log10 CFU/mL; 2.35 to 6.92 log10 CFU/mL and 1.72 to 6.83 log10 CFU/mL; and 1.64 to 7.17 log10 CFU/mL and 1.98 to 7.42 log10 CFU/mL from D0 to D12, respectively, for the N. latifolia and P. thonningii macerates. These contamination levels exceeded the values established by standards for pharmacopeia products. The pH of the macerates was acidic (4.92 to 6.5). Temperatures ranged from 25.7 to 32.7°C. Dissolved oxygen decreased from 3.6 to 1.2 mg/L. The physicochemical parameters influenced the proliferation of microorganisms. The microbiological quality of macerates is important, especially when used by young, elderly, or disease-weakened individuals.